Carthamus tinctorius seeds–Taraxacum coreanum combination attenuates scopolamine-induced memory deficit through regulation of inflammatory response and cholinergic function - He, Mei Tong; Shin, Yu-Su; Kim, Hyun Young; Cho, Eun Ju (Nutrition research and practice, 2024)
There is growing interest in herbal medicines for managing age-related diseases, such as Alzheimer's and Parkinson's. Safflower seeds ( L. seeds, CTS) and dandelions ( , TC) are widely used to treat bone- or inflammation-related diseases in Oriental countries. This study investigated the protective effect of the CTS-TC combination on scopolamine (Sco)-induced memory deficits through inflammatory response and cholinergic function. Moreover, marker components such as serotonin, -( -coumaroyl) serotonin, -feruloylserotonin, chlorogenic acid, and chicoric acid in the CTS-TC combination were analyzed for their potential benefits on memory function. Water extracts of CTS, TC, and the CTS-TC combination at various ratios (4:1, 1:1, and 1:4) (100 mg/kg) were orally administered to mice for 14 days. Sco (1 mg/kg) was intraperitoneally injected into the mice before each behavioral test. T-maze and novel object recognition tests were conducted to monitor behavioral changes after the treatment. Western blotting was performed to detect protein expression. In addition, the presence of 5 biomarkers, serotonin, -( -coumaroyl) serotonin, -feruloylserotonin, chlorogenic acid, and chicoric acid, was analyzed using high-performance liquid chromatography (HPLC). Behavioral tests showed that the CTS-TC combination enhanced memory function in Sco-injected mice. Inflammation-related proteins (inducible nitric oxide synthase, cyclooxygenase-2, and glial fibrillary acidic protein) were downregulated after treatment with the CTS-TC combination. The acetylcholinesterase protein expression was also downregulated. HPLC analysis revealed that -feruloylserotonin and chicoric acid were the predominant components, followed by -( -coumaroyl) serotonin, chlorogenic acid, and serotonin. These findings suggest that the CTS-TC combination protects against Sco-induced memory deficits by inhibiting inflammatory responses and cholinergic dysfunction. -feruloylserotonin and chicoric acid, along with -( -coumaroyl) serotonin, chlorogenic acid, and serotonin, might be biomarkers for the CTS-TC combination, and their effects on memory protection warrant further study.